2016
DOI: 10.1007/s10719-016-9696-9
|View full text |Cite
|
Sign up to set email alerts
|

Correlation among soluble receptors for advanced glycation end-products, soluble vascular adhesion protein-1/semicarbazide-sensitive amine oxidase (sVAP-1) and cardiometabolic risk markers in apparently healthy adolescents: a cross-sectional study

Abstract: In non-diabetics, low levels of soluble receptor for advanced glycations end products (sRAGE) associate with an increased risk of development of diabetes, cardiovascular afflictions, or death. The majority of studies in non-diabetics report an inverse relationship between measures of obesity, cardiometabolic risk factors and sRAGE and/or endogenous secretory RAGE (esRAGE) levels. To elucidate whether this inconsistency is related to the metabolically healthy obese phenotype, or a different impact of the risk f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
10
2
1

Year Published

2017
2017
2020
2020

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 14 publications
(14 citation statements)
references
References 64 publications
1
10
2
1
Order By: Relevance
“…In this cohort of healthy community‐dwelling adolescents, we did not find any correlation between markers of obesity, such as BMI or waist circumference, and circulating levels of CML or sRAGE, two commonly measured parameters of the AGE‐RAGE axis. This was in contrast to previous studies that showed decreased levels of CML and sRAGE when obese and lean children and adolescents were compared .…”
Section: Discussioncontrasting
confidence: 99%
See 1 more Smart Citation
“…In this cohort of healthy community‐dwelling adolescents, we did not find any correlation between markers of obesity, such as BMI or waist circumference, and circulating levels of CML or sRAGE, two commonly measured parameters of the AGE‐RAGE axis. This was in contrast to previous studies that showed decreased levels of CML and sRAGE when obese and lean children and adolescents were compared .…”
Section: Discussioncontrasting
confidence: 99%
“…In addition, a study in adolescents showed that soluble receptor for advanced glycation end products (sRAGE) was inversely correlated with the increasing number of components of metabolic syndrome in males but not in females . It has also been reported that a reduction in sRAGE precedes the development of metabolic syndrome . Few studies have been carried out in adolescents, which is a strategically important population, to establish long‐term lifestyle changes aimed at avoiding chronic medical conditions such as diabetes and cardiovascular disease.…”
Section: Introductionmentioning
confidence: 99%
“…Circulating sRAGE may act as decoy and ameliorate the response towards tissue destruction [33]. Despite that measures of obesity are considered as the most important determinants of low sRAGE levels [34], we did not observe significant betweengroup differences thereof. However, the recent study in healthy women showed that low sRAGE levels reflect accumulation of visceral fat mainly at the epicardial level and are present in advance of metabolic complications [35].…”
Section: Discussioncontrasting
confidence: 72%
“…Thus, if sRAGE levels mirror tissue RAGE expression, plasma sRAGE should be increased in obesity. In obese pre-pubertal children and adolescents esRAGE-to-sRAGE ratio remains constant (27,28). Thus, endogenous secretory and metalloproteinases-shaded isoforms of sRAGE decline proportionally.…”
Section: Discussionmentioning
confidence: 99%